Are you infected COVID-19? For Your Safety, Keep It Secret - Puspasari, Jehan; Rosliany, Nia; Silalahi, Malianti; Casman, Casman (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
The world is currently in a humanitarian crisis, with the effects of the COVID-19 pandemic creating a negative stigma in society toward people infected with COVID-19. Breastfeeding mothers are among the vulnerable groups, and they are not without stigma. The purpose of this study is to investigate the experiences of breastfeeding mothers who are positive for COVID-19 in carrying out self-quarantine. This qualitative study employs a phenomenological approach with a snowball sample selection. This research used a semi-structured approach to conduct in-depth interview. This study reached saturation in fifteen participants. Four themes appear related to  keeping a positive COVID-19 status secret was the best decision for safety. Themes that emerged from this research was that keeping a positive COVID-19 status secret was the best decision for safety. This theme emerges from the decision to keep it hidden as well as the reasons for doing so. The decision to keep it hidden was deemed appropriate in order to avoid the negative stigma that could lead to ostracization and blame from the community, family, and health workers.